Age relationships with telomere length, body weight and body length in wild dugong (Dugong dugon) - Cherdsukjai,Phaothep; Buddhachat,Kittisak; Brown,Janine; Kaewkool,Manthanee; Poommouang,Anocha; Kaewmong,Patcharaporn; Kittiwattanawong,Kongkiat; Nganvongpanit,Korakot (PeerJ, 2020)
The ability to estimate age and determine the growth status of free-ranging dugongs (Dugong dugon) is vital to providing insight into the basic biology of this endangered species. Currently, age estimation in dugong carcasses relies on counting dentin growth layer groups (GLGs) in tusks, but a disadvantage is they need to be intact. We explored whether measures of telomere length could be used as an alternative approach to age estimation in dugongs given that in other species, telomere length and age are inversely related. In this study, relative telomere length (rTL) was measured by qPCR in skin samples from 24 dugongs of varying ages determined by counts of GLGs. In addition, relationships between age by GLG counts and body weight and length and were examined. Our findings indicate that age estimated by GLGs was negatively correlated with telomere length using the logistic formula with a rate of telomere attrition of approximately 0.036 rTL/year between the ages of 5–20 years. By comparison, both body weight and length were positively correlated with GLG-based age, with growth rates of ~8.8 kg/year for weight and ~3.58 cm/year for length, respectively. After that, growth rates slowed substantially and then plateaued. The results suggest that physical maturity in dugongs occurs at 20 years of age and that measures of rTL might serve as a tool for age estimation in dugongs, living and deceased.
Keywords: Age; Growth; Telomere; Tusk; Senescence; Sirenia